Re-manajemen Akuntabilitas Panitia Tim Kerja: Upaya Peningkatan Outcomes Pelayanan Jemaat GPdI Beth Eden Kemayoran Jakarta Pusat Tahun 2022-2025 - Alexander Natan; Hutabarat Christiany; Nathanael Octavianus; Tarigan Mulina; Sihombing Lince; Sitompul Putra (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
This study examines the restructuring of accountability management for church task force committees in improving congregational ministry outcomes at GPdI Beth Eden Kemayoran, Central Jakarta. The study is motivated by the limited understanding of accountability in church ministry, which is often focused only on administrative responsibilities and activity reporting, reducing its role as an instrument for improving ministry quality. This research aims to analyze the implementation of accountability management restructuring for church task force committees based on Christian ministry principles and its implications for congregational ministry outcomes. The theological foundation is derived from 1 Corinthians 4:1–2, emphasizing that servants of Christ are stewards who must be faithful, and Ephesians 4:11–16, which highlights ministry as a means of equipping believers and building the body of Christ. This study employed a qualitative approach with a case study method at GPdI Beth Eden Kemayoran, Central Jakarta. Data were collected through interviews, observations, and document analysis and analyzed using a descriptive-interpretative approach. The findings show that restructuring accountability management strengthens coordination, clarifies ministry responsibilities, improves communication and collaboration, and encourages faithfulness, responsibility, and active participation among committee members. Accountability is not merely an administrative reporting mechanism but also functions as a process of spiritual formation, relational development, and ministry improvement. In conclusion, accountability management restructuring contributes significantly to enhancing congregational ministry outcomes from organizational, relational, and theological perspectives.